Analisis Keterjangkauan Dalam Aspek Harga Dan Aksesibilitas Obat Antihipertensi : Studi Implementasi Kebijakan Obat Nasional Di Dusun Belik Kabupaten Pemalang - Samira Anissa Azahrani; Atika Amorita Azza; Intan Amalia Putri; Isabel Hisni Ashara; Shinta Sintiana Dewi (JOURNAL SAINS STUDENT RESEARCH, 2026)
The National Drug Policy (KONAS) aims to guarantee the equitable availability and affordability of medicines for all communities. However, its implementation in remote areas still faces various constraints regarding drug affordability. This study aims to evaluate the price affordability and accessibility of antihypertensive medicines as a form of KONAS implementation in Dusun Belik, Bodas Village, Watukumpul District, Pemalang Regency. This study utilized a qualitative method with a cross-sectional approach. Data were obtained through observation, interviews, and documentation involving hypertensive patients selected using a purposive sampling technique. The results indicated that the nominal price of antihypertensive medicines consumed by the community is considered affordable. However, this affordability decreases when transportation costs to obtain the medicines are taken into account. Furthermore, most respondents experience difficulties in obtaining their medication routinely due to the long distance to healthcare facilities and inadequate road infrastructure conditions. Consequently, this leads to medication non-adherence (discontinuation) in several patients, which potentially increases the risk of hypertensive complications. In conclusion, the implementation of KONAS in ensuring the availability and affordability of antihypertensive medicines in Dusun Belik has not been achieved optimally.